Tartrolon E rapidly blocks Toxoplasma gondii capacity to invade host cells - Fernanda G. Fumuso; Jason A. Clement; Matthew J. Todd; Roberta M. O'Connor (International Journal for Parasitology: Drugs and Drug Resistance)
Toxoplasmosis is a worldwide parasitic disease caused by the apicomplexan Toxoplasma gondii. Severe neurological illness occurs in immunosuppressed patients, and congenital disorders can follow transplacental primo infection during pregnancy. New effective antiparasitic drugs are needed since chronic cystic stages are resistant to current available treatments, and some of the congenital infections are unresponsive to available therapeutics. Tartrolon E (trtE) is a marine secondary metabolite that has high selectivity against human and animal apicomplexan parasites including T. gondii, Cryptosporidium parvum and Plasmodium falciparum. We evaluated the effect of the compound on extracellular tachyzoite viability, morphology, membrane permeability and its ability to block host cell attachment and/or invasion. While 80 % of T. gondii infective capacity is blocked after only 30 min of compound treatment, parasite viability, morphology, membrane integrity and host cell attachment were unaffected until after 4 h of treatment. These effects were irreversible when parasites were allowed to infect host cells after trtE treatment. Drug exposure for more than 4 h significantly affected tachyzoite survival and altered parasite morphology. The mechanism of action of trtE is still unknown but includes blocking parasite invasion processes. Further research is needed to determine the molecular target of trtE to further progress the compound as an antiparasitic candidate.